Profile of Students of Sports Science Study Programs in 2023 - Marnex Willner Standing (International Journal on Integrated Education, 2023)
Cardiopulmonary endurance is the ability of the heart, lung and blood vessel systems to function optimally while carrying out daily activities for a long time without experiencing significant fatigue. This research focused on "cardiac endurance profile of sports science study program students in 2023. This study aims to find out about the profile of cardiopulmonary endurance students of sports science study program in 2023. This type of research is a descriptive type of research. The instrument used in this research is the Cooper test. The sample in this study were 30 people using simple random sampling technique or simple random sampling. The data analysis technique used in this research is descriptive data analysis technique using SPSS. The results of the study conducted by cardiopulmonary endurance were very poor category 11 people (11.37%), less category 13 people (13.43%), medium category 1 person (1.3%), good category 5 people (5, 17%). In order to obtain good fitness, intensive and regular training should be carried out so that an exercise program will be obtained that is in accordance with the objectives of the exercise program, which are still classified as lacking and very lacking, it is necessary to increase exercise in order to achieve good fitness.